Livestreaming, interactive, group movement classes to address social isolation and well‐being in people living with memory loss and their caregivers. (1st February 2022) - Nicosia, Francesca M; Lee, Jennifer Ann; Chesney, Margaret A; Mehling, Wolf; Sudore, Rebecca L; Barnes, Deborah
Abstract: Background: Non‐pharmacologic programs can improve function and quality of life in people with memory loss (PWML), but in‐person programs are not available in many communities. We previously developed the interactive, livestreaming, group‐based, Moving Together TM program for PWML and their caregivers (CGs). This study assesses feasibility, satisfaction, and qualitative outcomes in four groups that participated during the COVID‐19 pandemic. Method: We assessed feasibility based on number of participants and attendance. We administered an online survey at the end of the 12‐week program to assess satisfaction. The survey included a 6‐item Class Experience scale (e.g., feeling accepted, energized) and the 4‐item PROMIS Social Isolation scale, both using 4‐point Likert response scales. Open‐ended questions asked about changes noticed in themselves and others during the program. We used a previously established coding scheme informed by a biopsychosocial framework to code free‐text survey responses and refined codes as we identified new concepts. Results: We offered four 12‐week class series (1 hour, 2 days/week) from April to July 2020 that included 8 to 14 participants each (total N =39: 24 PWML, 15 CGs). Average attendance was 78% (range: 58% to 98%). Surveys were sent to 31 participants who completed the program, of whom 25 (16 PWML, 9 CGs) responded. Nearly all respondents reported that they often, mostly or always felt acceptance and well‐being during classes (6‐items, 88% to 100%), and most reported that they rarely or never felt social isolation (4 items, 50% to 100%). Qualitative analyses of free‐text responses identified self‐reported improvements in both PWML and CGs in several areas: 1) emotional well‐being, including better mood, lower stress, and increased relaxation; 2) social connection, such as friendship and camaraderie; 3) physical function, including more energy, increased activity, improved movement, and increased mind‐body awareness; and 4) cognitive function such as better focus. Conclusion: This study demonstrates that the interactive, livestreaming, group‐based, Moving Together TM program is feasible and associated with high satisfaction among both PWML and their CGs. Technology offers tremendous potential to increase accessibility to evidence‐based, non‐pharmacologic programs that people with memory loss (PWML) and caregivers (CGs) can participate in from the safety of their homes.